2008
DOI: 10.1002/mrd.20972
|View full text |Cite
|
Sign up to set email alerts
|

Differential ovarian expression of KiSS‐1 and GPR‐54 during the estrous cycle and photoperiod induced recrudescence in Siberian hamsters (Phodopus sungorus)

Abstract: Kisspeptins, coded by the KiSS-1 gene, regulate aspects of the reproductive axis by stimulating GnRH release via the G protein coupled receptor, GPR54. Recent reports show that KiSS/GPR54 may be key mediators in photoperiod-controlled reproduction in seasonal breeders, and that KiSS-1/GPR54 are expressed in the hypothalamus, ovaries, placenta, and pancreas. This study examined the expression of KiSS-1/GPR54 mRNA and protein in ovaries of Siberian hamsters (Phodopus sungorus). Ovaries from cycling hamsters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 55 publications
2
47
0
1
Order By: Relevance
“…Interestingly, in these studies it was observed that kiss1 mRNA expression occurs in a cyclic manner during the oestrous cycle with a significant increase at the preovulatory stage, which could be prevented by attenuating preovulatory LH surge and could be restored by hCG treatment [154]. Similar results were observed in indomethacintreated rats and photo-inhibited hamsters [155,157]. Additionally, recent studies on kiss1r heterozygous and knockout mice models further provide strong evidence in favour of the direct role of kisspeptins in the ovary by revealing that the loss of one kiss1r allele resulted in premature ovarian failure and loss of both kiss1r alleles blocked maturation of ovarian follicles and ovulation, which could not be rescued by gonadotrophins administration [159][160][161].…”
Section: Female Reproductive Tractsupporting
confidence: 57%
See 1 more Smart Citation
“…Interestingly, in these studies it was observed that kiss1 mRNA expression occurs in a cyclic manner during the oestrous cycle with a significant increase at the preovulatory stage, which could be prevented by attenuating preovulatory LH surge and could be restored by hCG treatment [154]. Similar results were observed in indomethacintreated rats and photo-inhibited hamsters [155,157]. Additionally, recent studies on kiss1r heterozygous and knockout mice models further provide strong evidence in favour of the direct role of kisspeptins in the ovary by revealing that the loss of one kiss1r allele resulted in premature ovarian failure and loss of both kiss1r alleles blocked maturation of ovarian follicles and ovulation, which could not be rescued by gonadotrophins administration [159][160][161].…”
Section: Female Reproductive Tractsupporting
confidence: 57%
“…The initial evidence regarding the presence of kisspeptin and its receptor on the ovaries and uterus came from studies done on rats [153], which was later confirmed by immunohistochemical analysis performed in other species including humans [154][155][156][157][158]. Interestingly, in these studies it was observed that kiss1 mRNA expression occurs in a cyclic manner during the oestrous cycle with a significant increase at the preovulatory stage, which could be prevented by attenuating preovulatory LH surge and could be restored by hCG treatment [154].…”
Section: Female Reproductive Tractmentioning
confidence: 92%
“…Total RNA from ovaries was isolated using Trizol LS reagent (Invitrogen Life Technologies, Carlsbad, CA) as per manufacturer protocol and as described previously (Shahed and Young, 2009). One μg of total RNA was first treated with DNase 1 (1 unit/μl) and incubated for 10 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated from ovarian tissue with Trizol (Invitrogen, Carlsbad, CA) and cDNA was synthesized exactly as described before (Shahed & Young, 2009). Primers were designed using Siberian hamster sequences (PCR products extracted and sequenced as described Shahed & Young, 2009) and OligoPerfect Designer software (Invitrogen) using the MX3000 cycler manual design criteria (Stratagene Corp., Cedar Creek, TX). Primer sequences used were: MMP-2 (forward) ATG ATG TCA GCT TCC CCA TC; MMP-2 (reverse) ACC TGG ACC CTG AAA CAG TG ; MMP-9 (forward) ACT TTG GAA ACG CAA ATG GT ; MMP-9 (reverse) AGT CTC TCA CTG GGG CAG AA .…”
Section: Methodsmentioning
confidence: 99%